Pendampingan Belajar Matematika dalam Meningkatkan Minat Belajar Peserta Didik pada Materi Bilangan Bulat di SMP Citra Bakti - Tali Wangge, Maria Carmelita; Bela, Maria Editha; Wewe, Melkior; Bhoke, Wilibaldus; Lewa, Yusta Selvianjeli; Key, Katarina Karmelita; Jodo, Dominikus Kaka; Lola, Teofania Kristina; Wea, Marselina; Woli, Roslinantia (Abdimas Indonesian Journal, 2024)
Educition is conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual, religious stength, self-control, personality, intellgence, noble morals and the skills needed by themselves and society. The low learning ability of students in mathematucs lessons is due to a lack of interest and willinness to learn, students towards assistance activity for Citra Bakti Middle School students aims to increase interest and for student in mathematics lessons. Learning assintance for students in mathematics lessons is carried out face to face and is carried out at school every mathematics lesson hour. The method used is direct observation at the Citra Bakti Ngada Primary School. The observation method was chosen to target of this activity and assintance is students of cllas VII Citra Bakti Midlle School. With the prensence of mentoring activities, students interest learn IM. This in learning about integer material increases, students response can be seen from abilities in the process of mentoring activities, students can.